618. Pharmacokinetic/pharmacodynamic analysis of combination therapy with continuous infusion (CI) fosfomycin plus extended-infusion (EI) or CI beta-lactams for treating documented carbapenem-resistant Gram-negative bloodstream infections and/or hospital-acquired pneumonia: a case series. (15th December 2022) - Gatti, Milo; Rinaldi, Matteo; Cojutti, Pier Giorgio; Horna, Clara Solera; Fornaro, Giacomo; Viale, Pierluigi; Giannella, Maddalena; Pea, Federico
Abstract: Background: To describe the pharmacokinetic/pharmacodynamic (PK/PD) behaviour and the microbiological outcome of combination therapy with continuous infusion (CI) fosfomycin plus extended-infusion (EI) or CI beta-lactams for treating severe carbapenem-resistant Gram-negative (CR-GN) infections. Methods: Single-center retrospective study of patients who were treated with CI fosfomycin plus EI or CI beta-lactams for severe CR-GN infections and who underwent therapeutic drug monitoring (TDM), from 01 April 2021 to 31 January 2022. Concentrations of CI fosfomycin, meropenem and ceftazidime-avibactam were determined at steady-state (Css ), while those of EI cefiderocol were measured at trough (Cmin ). The desired joint PK/PD targets of combination therapy were considered as optimal when simultaneously the area-under-the curve to minimum inhibitory concentration (AUC/MIC) ratio for fosfomycin was > 83 and the Css /MIC for meropenem or for ceftazidime-avibactam or the Cmin /MIC ratio for cefiderocol was > 4 (quasi-optimal if only one of the two was achieved, and suboptimal if none of the two was achieved). Relationship between the joint PK/PD targets and microbiological failure (MF) defined as isolation of the same pathogens from follow-up blood cultures or BAL and assessed within 30 days of treatment onset, was investigated. Results: Among the 16 retrieved patients with documented CR-GN infections, 12 underwent TDM of both fosfomycin and beta-lactams, and seven out of these (3 HAP, 3 BSI+HAP, and one BSI) had determination of fosfomycin MIC determined by agar-dilution (see Table). The joint PK/PD targets were optimal in 4 cases and quasi-optimal in the other 3y. MF occurred in two patients (29%) who were affected by HAP, received combination therapy with ceftazidime-avibactam, and achieved only quasi-optimal joint PK/PD targets (with fosfomycin AUC/MIC < 83). No MF occurred in patients with optimal joint PK/PD targets. Summary of the relationship between PK/PD targets and microbiological failure in patients receiving combination therapy with CI fosfomycin plus EI/CI beta-lactams Conclusion: CI fosfomycin in combination with EI/CI beta-lactams may allow for the achievement of optimal joint PK/PD targets in most patients with CR-GN infections, and may represent a potential strategy for minimizing the risk of MF. Disclosures: All Authors : No reported disclosures.